A obra vocal de estércio Marquez Cunha: especificidades da música e memória musical no cenário goianiense - Carvalho, Leonardo Victtor de (2012)
This study aimed to verify how the construction of the specifics of music in the classical dimension of goianiense society, as well as the possible interactions of this construction with other cultural dimensions, from analysis and interpretation of a case study: three works selected vocal repertoire from goiano composer Estércio Marquez Cunha, members of the CD "Lento Acalanto" 1999. The crossing of the concrete object with the four basic processes of music - creating, receiving, production and circulation - with emphasis on the first two, based on the conception that elects, by a bias, the "autonomy of the work" and, secondly, "work as symbolic structure”, two “constructions" that were the basis of the different times that the Western Society instituted in its historical trajectory, gave greater scope for research, allowing the focus on" form "and, concomitantly, the symbolic implications of this "form" the social fabric. The systematization of this initiative required the achievement of interdisciplinary work in three stages, starting with the conceptual approach of the specifics of the music, its basic processes and processes-historical paradigm, followed by the case study on the composer Estércio Marquez Cunha, and his work interaction with the goianiense music scene and finally the musical analysis of selected works. Achieving these steps and retro-analysis of the entire process allow us to affirm that the specifics of music could be observed in part from this case study. Estércio Cunha's work is really restricted to the field of classical music production in Goiânia. There has met the specific circumstances related to creative processes and reception, has circulated, above all, from the composer's connection with academic institutions, especially the Escola de Música e Artes Cênicas from UFG, which has circulated social representations. In this context, based on these representations, has become a force in terms of symbolic capital, capable of showing works and practices that incorporate the habitus that circulates in this specific field of music production. On the other hand, has established itself as economic capital, and has not shown a meaningful dialogue with other fields of music production. The analysis and interpretations that were the basis of the basic processes focused approach proved efficient when crossing formalist analysis and symbolic.